Internal Marketing in Today’s Organization - Biesaga-Słomczewska, Elżbieta J.; Iwińska-Knop, Krystyna (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Internal marketing is an interesting area of scientific reflection on the role of the human factor in building the market success of an organisation, unfortunately, so far it has not been frequently undertaken by researchers. Although its importance for the development of management sciences and business practice is undisputed, so far it has not been widely reflected in scientific literature, which results from the complicated nature of research and the need to grasp the essence of internal marketing from various points of view: psychological, sociological, economic, legal, or managerial. The perspective proposed by the author places considerations in human resources management, because the origins of the concept of internal marketing come from this area - very resistant to introducing changes, especially innovative management solutions. There are many reasons for this, one of which is the lack of expected results in the short term. The approach to the human factor is still based on the traditional perception of its roles in the organisation, which does not match the contemporary conditions resulting from the dynamics of changes in the environment. Internal marketing meets the "weaknesses" of human management, but in order for it to become effective in practice - it is necessary to verify the behaviour of both superiors and employees so far - their ways of thinking and habits leading to overcoming the previous stereotypes concerning the "employer-subordinate" relationship. This requires a marketing approach to the management instruments used to perform a personal function and the recognition of employees as internal customers, to whom the organization should identify needs and expectations in order to take adequate action leading to satisfaction, commitment and creation of loyalty to the company. Therefore, the intention of the authors was to pay special attention to innovative activities that cause proactive attitudes of employees in the scope of: building internal organisational relations, exchanging values, which the parties care about - using the negotiated dimension of agreeing on positions, methods of communication or creating value for the stakeholders. This publication is conceptual and mainly based on a critical analysis of scientific literature, taking into account the possibilities of implementing the assumptions of internal marketing in practice. It is mainly dedicated to the management staff of various levels - from managers to persons occupying the highest positions in companies, as well as to research workers, students of economic and management faculties, or sociology and psychology, and all persons whose intention is to improve their management competences.